The Clinical and Prognostic Impact of the Choice of Surgical Approach to Fourth Ventricular Tumors in a Single-Center, Single-Surgeon Cohort of 92 Consecutive Pediatric Patients - Onorini, Nicola; Spennato, Pietro; Orlando, Valentina; Savoia, Fabio; Calì, Camilla; Russo, Carmela; De Martino, Lucia; de Santi, Maria Serena; Mirone, Giuseppe; Ruggiero, Claudio; Quaglietta, Lucia; Cinalli, Giuseppe (Frontiers in Oncology, 2022)
Objective: A single-institution cohort of 92 consecutive pediatric patients harboring tumors involving the fourth ventricle, surgically treated via the telovelar or transvermian approach, was retrospectively reviewed, in order to analyze the impact of surgical route on surgery-related outcomes and cumulative survival. Methods: Clinical, radiological, surgical and pathology details were retrospectively analyzed. We selected n=6 surgery-related clinical and radiological outcomes: transient and permanent neurological deficits, duration of assisted ventilation, postoperative new onset medical events, postoperative cerebellar mutism, extent of resection. We built univariate and multivariate logistic models to analyze the significance of relationships between the surgical routes and the outcomes. Cumulative survival (CS) was estimated by the cohort approach. Results: There were 53 girls and 39 boys (mean age: 83 months). Telovelar approach was performed in 51 cases and transvermian approach in 41 cases. Early post-operative MRI studies showed complete removal in 57 cases (62%) and measurable residual tumor in 35 cases (38%). The average tumor residual volume was 1,316 cm3 (range: 0,016-4,231 cm3; median value: 0,9875 cm3). Residual disease was more often detected on immediate post-op MRI after telovelar approach, but the difference was not significant. Cerebellar mutism was observed in 10 cases (11%). No significant difference in the onset of cerebellar mutism was detected between telovelar and transvermian approach. The choice of surgical approach did not significantly modify any other postoperative outcome and 1-year/3-years CS of high-grade surgically treated tumors. Conclusions: With the limitation of a single-center, single-surgeon retrospective series, our findings offer significant data to reconsider the real impact of the choice of the surgical route to the fourth ventricle on the incidence of cerebellar mutism and surgery-related morbidity. This seem to be in line with some recent reports in the literature. Surgical approach to the fourth ventricle should be individualized according with the location of the tumor, degree of vermian infiltration, lateral and upward extension. Telovelar approach and transvermian approach should not be considered alternative but complementary. Pediatric neurosurgeons should fully master both approaches and choose the one he considers the best for the patient according with a thorough and careful evaluation of pre-operative imaging.